Considering Efficacy and Cost, Where Does Ramucirumab Fit in the Management of Metastatic Colorectal Cancer?. (11th August 2015) - Goldstein, Daniel A.; El-Rayes, Bassel F.
Abstract : Health care institutions, physicians, and patients can—and should—be more involved in evaluating the role of new therapies such as ramucirumab in metastatic colorectal cancer based on their value. This is especially true in the case of a treatment that adds no additional benefit in terms of efficacy or toxicity compared with the current standard of care and has a higher cost.